PENGEMBANGAN PEMBELAJARAN TARI LENGGOK MAK INANG MELALUI MULTIMEDIA INTERAKTIF BERBASIS E-LEARNING - Ronni Lirahman; Yusnizar Heniwaty Heniwaty (Universitas Negeri Medan, 2019)
ABSTRACT This research produced a product of the development of Lenggok Mak Inang dance learning through interactive multimedia which included appreciation learning material (Basic Competence 3) and expression (Basic Competence 4) in class X of SMK / SMA. The appreciation material contains the definition of dance, accompaniment music, clothing, patterns, while the expression material contains terms, variety and arrangement of motion in the Lenggok Mak Inang dance. From the test media experts got a score of 4,42 (Very Good), media experts got a score of 4 (Good), user trials which included an initial field trial of 4,08 (Good), main field trial 4,22 ( Very Good) and an operational field trial of 4,53 (Very Good). The results obtained indicate that the development of interactive multimedia learning Lenggok Mak Inang dance is very feasible to use or be used as a learning media for dance. Keywords: Interactive Multimedia, E-Learning, Lenggok Mak Inang Dance. ABSTRAKPenelitian ini menghasilkan produk pengembangan pembelajaran tari Lenggok Mak Inang melalui multimedia interaktif yang didalamnya terdapat materi pembelajaran apresiasi (Kompetensi Dasar 3) dan ekspresi (Kompetensi Dasar 4) kelas X SMK/SMA. Materi apresiasi berisikan definisi tari, musik pengiring, busana, pola/ garis, sedangkan materi ekspresi berisikan istilah, ragam dan susunan gerak pada tari Lenggok Mak Inang. Dari uji ahli media mendapatkan skor 4,42 (Sangat Baik), ahli media mendapatkan skor 4 (Baik), uji coba pengguna yang meliputi uji coba lapangan awal 4,08 (Baik), uji coba lapangan utama 4,22 (Sangat Baik) dan uji coba lapangan operasional 4,53 (Sangat Baik). Hasil yang diperoleh menunjukkan bahwa pengembangan multimedia interaktif pembelajaran tari Lenggok Mak Inang ini Sangat Layak digunakan atau dijadikan media pembelajaran tari. Kata kunci: Multimedia Interaktif, E-Learning, Tari Lenggok Mak Inang.